The (G'/G)-expansion method for abundant traveling wave solutions of Caudrey-Dodd-Gibbon equation - Naher, Hasibun; Abdullah, Farah Aini; Akbar, M. Ali (© 2011 Mathematical Problems in Engineering, 2016)
This article was published in the Mathematical Problems in Engineering [© 2011 Hasibun Naher et al.] and the definite version is available at : http://dx.doi.org/10.1155/2011/218216 The Journal's website is at: https://www.hindawi.com/journals/mpe/2011/218216/